Evaluation of a Hyperbaric Oxygen Therapy Intervention in Individuals with Fibromyalgia. Issue 6 (16th February 2021) - Curtis, K; Katz, J; Djaiani, C; O'Leary, G; Uehling, J; Carroll, J; Santa Mina, D; Clarke, H; Gofeld, M; Katznelson, R
Abstract: Objective: To evaluate the feasibility and safety of hyperbaric oxygen therapy (HBOT) in patients with fibromyalgia (FM). Design: A cohort study with a delayed treatment arm used as a comparator. Setting: Hyperbaric Medicine Unit, Toronto General Hospital, Ontario, Canada. Subjects: Eighteen patients diagnosed with FM according to the American College of Rheumatology and a score ≥60 on the Revised Fibromyalgia Impact Questionnaire. Methods: Participants were randomized to receive immediate HBOT intervention (n = 9) or HBOT after a 12-week waiting period (n = 9). HBOT was delivered at 100% oxygen at 2.0 atmospheres per session, 5 days per week, for 8 weeks. Safety was evaluated by the frequency and severity of adverse effects reported by patients. Feasibility was assessed by recruitment, retention, and HBOT compliance rates. Both groups were assessed at baseline, after HBOT intervention, and at 3 months' follow-up. Validated assessment tools were used to evaluate pain, psychological variables, fatigue, and sleep quality. Results: A total of 17 patients completed the study. One patient withdrew after randomization. HBOT-related adverse events included mild middle-ear barotrauma in three patients and new-onset myopia in four patients. The efficacy of HBOT was evident in most of the outcomes in both groups. This improvement was sustained at 3-month follow-up assessment. Conclusion: HBOT appears to be feasible and safe for individuals with FM. It is also associated with improved global functioning, reduced symptoms of anxiety and depression, and improved quality of sleep that was sustained at 3-month follow-up assessment.